2012
DOI: 10.1051/epjconf/20123817001
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the influence of incomplete fusion on complete fusion of16O induced reactions at moderate excitation energies

Abstract: Abstract. An attempt has been made to investigate for the reaction dynamics leading to incomplete fusion (ICF) of heavy ions at moderate excitation energies, especially the influence of incomplete fusion on complete fusion (CF) of 16 O induced reactions at specific energies. Excitation functions (EFs) of various reaction products populated via CF and/or ICF of 16 O projectile with 45 Sc target were measured at energies ≈3-7 MeV/nucleon, using recoil catcher technique followed by offline γ-ray spectroscopy.The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…have been a point of interest even at energies as low as 5 MeV/A. Recent studies report breakup of 12 C, 16 O and 20 Ne into 4 He, 8 Be and 12 C projectile fragments and their incomplete fusion with the target [1][2][3][4][5]. Long back, in 1950, Ghoshal in his famous experiment showed that proton and alpha projectiles forming the same compound nucleus decay similarly and thus corroborate the Bohr compound nucleus assumption [6].…”
Section: Introductionmentioning
confidence: 99%
“…have been a point of interest even at energies as low as 5 MeV/A. Recent studies report breakup of 12 C, 16 O and 20 Ne into 4 He, 8 Be and 12 C projectile fragments and their incomplete fusion with the target [1][2][3][4][5]. Long back, in 1950, Ghoshal in his famous experiment showed that proton and alpha projectiles forming the same compound nucleus decay similarly and thus corroborate the Bohr compound nucleus assumption [6].…”
Section: Introductionmentioning
confidence: 99%
“…Study of nuclear reaction around the barrier energy involves the investigation of complete and incomplete fusion processes and their dependence on various entrance channel parameters [5][6][7][8]. Complete fusion (CF) requires a total transfer of incident momentum from projectile to compound nucleus through the fusion of entire projectile's mass with the target.…”
Section: Introductionmentioning
confidence: 99%
“…Since then, the study of projectile break-up and its effect on CF suppression has become an active topic of research [6]- [8]. In recent years, it has been observed that for low Z-projectiles (Z ≤ 10), e.g., 12 C, 16 O and 20 Ne, with incident energies slightly above the Coulomb barrier, interacting with medium and heavy mass targets, both the CF and ICF processes may be considered as the dominant reaction mechanism [9]- [14]. CF has been experimentally defined as the capture of total charge or mass of the incident projectile by the target nucleus.…”
Section: Introductionmentioning
confidence: 99%